The Nexus Between CAMELS Index Toward Net Profit - Fatichatur Rachmaniyah; Arief Yuswanto Nugroho; Muhamad Iqbal Fasa (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2021)
This study aims to determine whether the CAMELS variable can affect the net profit generated by Bank Mualamalat simultaneously and partially. CAMELS variables include: Capital Adequency Ratio (CAR), NonPerforming Financing (NPF), Net Profit Margin (NPM), Net Operating Margin (NOM), Financing to Deposit Ratio (FDR), Net Open Position (NOP). This study used quarterly financial data for the years 2012 - 2019. Data analysis techniques used multiple linear regression analysis. The results of the F test, the CAMELS variable simultaneously show that significant affect on net profit with adjusted R square 64%. In the t test, partially CAR and PDN variables significantly influence on net profit, but the NPF, NPM, NOM, and FDR variables did not have effect on net profit.